Metabolic dysfunction‐associated fatty liver disease directly related to liver fibrosis independent of insulin resistance, hyperlipidemia, and alcohol intake in morbidly obese patients. Issue 10 (6th August 2022) - Inamine, Susumu; Kage, Masayoshi; Akiba, Jun; Kawaguchi, Takumi; Yoshio, Sachiyo; Kawaguchi, Machiko; Nakano, Dan; Tsutsumi, Tsubasa; Hashida, Ryuki; Oshiro, Kouichi
Abstract: Aim: Hepatic fibrosis is associated with various factors, including metabolic dysfunction‐associated fatty liver disease (MAFLD), insulin resistance, and alcohol intake in patients with morbid obesity. We investigated factors directly associated with hepatic fibrosis in patients with morbid obesity using a graphical model. Methods: We enrolled 134 consecutive patients with morbid obesity who underwent liver biopsy during sleeve gastrectomy (median age 43.5 years; MAFLD 78.4%; homeostasis model assessment of insulin resistance [HOMA‐IR] 5.97; >20 g/day alcohol intake 14.2%). Patients were classified into none/mild (F0/1; n = 77) or significant/advanced fibrosis (F2/3; n = 57) groups, based on histology. Factors associated with F2/3 were analyzed using logistic regression analysis and a graphical model. Results: F2/3 was observed in 42.5% of the enrolled patients. The prevalence of MAFLD and HOMA‐IR values were significantly higher in the F2/3 group than in the F0/1 group; however, no significant difference in alcohol intake was observed between the two groups. On logistic regression analysis, MAFLD, but not HOMA‐IR or alcohol intake, was the only independent factor associated with F2/3 (odds ratio 7.555; 95% confidence interval 2.235–25.544; p = 0.0011). The graphical model revealed that F2/3 directly interacted with MAFLD, diabetes mellitus, HOMA‐IR, and low‐density lipoprotein cholesterol. Among these factors, MAFLD showed the strongest interaction with F2/3. Conclusions: We determined that MAFLD was more directly associated with significant/advanced fibrosis than insulin resistance or hyperlipidemia, and alcohol intake was not directly associated with hepatic fibrosis. Metabolic dysfunction‐associated fatty liver disease could be the most important factor for hepatic fibrosis in patients with morbid obesity.